Association of serum uric acid level with coronary artery stenosis severity in Korean end-stage renal disease patients [Volume 36, Issue 3, September 2017, Pages 282-289] - Hye Yun Jeong; Hye Jeong Cho; Sang Hoon Kim; Jun Chul Kim; Mi Jung Lee; Dong Ho Yang; So-Young Lee (The Korean Society of Nephrology, 2018)
The authors would like to publish this corrigendum to clarify the roles of some authors in the above article (https://doi.org/10.23876/j.krcp.2017.36.3.282). Hye Yun Jeong and Hye Jeong Cho contributed equally to the above study as co-first authors.